Pengaruh Pemberian Pupuk Kandang Kotoran Kambing Dan Berbagai Komposisi Pupuk Npk Terhadap Pertumbuhan Dan Produksi Bawang Merah (Alium ascalonicum. L) - taufikurrahman taufikurrahman; Sugiarto Sugianto; Siti Asmaniyah Mardiyani (AGRONISMA, 2021)
Shallots are one of the superior vegetable commodities that have been continuously cultivated by farmers for a long time. The community's need for shallots will continue to increase along with the increase in population. This study aims to determine the effect of the combination of goat manure fertilizer at various doses and various types of NPK fertilizer composition on the growth and production of shallots. This study used a randomized block design (RAK) which was arranged in a factorial manner with 2 factors. Factor 1 uses a dose of manure, factor 2 uses a composition of NPK fertilizer with the same dose. The results showed that giving a dose of goat manure combined with NPK fertilizer composition could increase the growth and production of shallots both in height, number of leaves and leaf area, the best treatment was P1K3 treatment (Given with NPK fertilizer (12-11-20) 300 kg/ha given goat manure 15 tons/ha) with an average tuber weight of 9.65 tons/ha. The dose of goat manure 15 tons/ha can increase the production of shallots with an average tuber weight of 9.65 tons/ha. The application of NPK petro aristocratic fertilizer composition of 300 kg/ha can increase the production of shallots in the P1K3 treatment (Given with NPK fertilizer (12-11-20) 300 kg/ha given goat manure 15 tons/ha) with an average tuber weight of 9.65 tons/ha.